Next-generation sequencing of CCR5, CXCR4, and IFNAR1 variants in relation to HIV-1 disease progression and ART response - Kubra Cigdem Pekkoc-Uyanik; Zeynep Gizem Todurga-Seven; Andleeb Shahzadi; Haktan Sonmez; Sevcan Mercan; Bilgul Mete; Fehmi Tabak (Scientific Reports)
Abstract HIV, which causes acquired immune deficiency syndrome (AIDS), invades the host cell via the CD4 receptor and CCR5 or CXCR4 co-receptors. Interferons induced early in HIV infection induce an antiviral defense mechanism through IFNAR signaling. Our study aimed to examine the relationship between CCR5, CXCR4, and IFNAR1 gene variations as a risk factor in HIV + patients and their response to their clinical parameters. Targeted next-generation sequencing (tNGS) was used to perform molecular genotyping analysis of the CCR5, CXCR4, and IFNAR1 genes in genomic DNA from 22 HIV + patients and 25 healthy individuals as controls. We detected 13 rare mutations in the study, including 3 missense, 1 synonymous, 2 5′UTR, 4 3′UTR, and 1 frameshift variation. We also analyzed 6 common variants in the IFNAR1 and CXCR4 genes. HIV + patients carrying the homozygous TT genotype of the IFNAR1 intronic rs2856973:T > A variant had higher CD4 + T cell counts compared with patients carrying the TA + AA genotypes of the rs2856973 variant in the naive and first month of the ART (p = 0.001 and p = 0.001, respectively). Similarly, participants receiving ART with a TT genotype of rs2856973:T > A showed a significantly higher CD4 + T cell count in the third month (p = 0.001). Patients carrying the homozygous wild-type genotype of the CXCR4 intronic rs2680880:A > T SNP had lower CD4 + T cell count compared with subjects carrying the AT + TT mutant genotypes of rs2680880:A > T in the naive and first-month period (p = 0.015 and p = 0.025, respectively). Our results demonstrate that intronic variations in the IFNAR1 rs2856973:T > A and CXCR4 rs2680880:A > T genes can contribute to modifications in HIV progression and CD4 + T recovery under ART.